Stability of two-dimensional sediment flow down an inclined plane - Diep, Nguyen Van; Chung, Dang Huu (Vietnam Journal of Mechanics, 1992)
In this paper the authors have studied the instability of 2-D flow with sediment transport, which is based on the generalized diffusion theory. The authors have constructed the boundary conditions of the bed concentration and diffusion flux at the free surface for dosing equations system. After that the authors have considered the instability and obtained the neutral-curve of stability in the plane (R1 k). The obtained results show that if there is no suspended sediment, the result will be identical to Chia-Shun Yih's.